Body sensor network mobile solutions for biofeedback monitoring - Pereira, Orlando (2013)
Body sensor networks (BSN) appeared as an application of Wireless Sensor Networks (WSN) to medicine and biofeedback. Such networks feature smart sensors (biosensors) that capture bio-physiological parameters from people and can offer an easy way for data collection. BSNs also need suitable interfaces for data processing, presentation, and storage for latter retrieval. As a result, Bluetooth technology can be used to communicate with several more powerful and graphical user interface (GUI)-enabled devices such as mobile phones or regular computers. Taking into account that people currently use mobile and smart phones, it offers a good opportunity to propose a suitable mobile system for BSN networks. This paper presents a BSN mobile solution for biofeedback monitoring using the four major smart phone platforms: Symbian, Windows Mobile, Android, and iPhone. As case study, a sensing health with intelligence modularity, mobility and experimental reusability (SHIMMER) platform with a core-body temperature sensor enabled to construct the BSN was used. The four mobile applications were evaluated and validated, and are ready for use.